Factor influencing decision for eye screening among diabetes patients: a review - Mat Isa, Rifatunnailah; Saidi, Sanisah; Salam, Adzura; Jamaludin, Thandar Soe Sumaiyah (MedWin Publishers, 2020)
Introduction: Individuals with Diabetes Mellitus (DM) are at increased risk for developing diabetic ocular complications. Materials and Methods: A systematic approach was applied to find the relevant topic regarding the said issue. This literature review aimed to determine the system of eye screening, reasons for seeking eye screening and their treatment. Results: A total of 22 papers and one guideline were reviewed in this study. There were four main barriers found in this study regarding with factor influencing decision for eye screening among diabetes patients. Those were diabetic eye screening, management issues on diabetic eye screening and barriers to uptake diabetic eye screening. The details of these finding results were discussed further in the discussion section. Conclusion: The health care system, health care provider and patients itself could provide a clear explanation of factors influencing the decision for diabetic eye screening. A further study is recommended to validate these review findings